2017
DOI: 10.22159/ajpcr.2017.v10i8.18539
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Resistance Pattern of Pseudomonas Aeruginosa Isolated From Clinical Samples at a General Hospital in Padang, West Sumatra, Indonesia

Abstract: Objectives: Pseudomonas aeruginosa is an opportunistic pathogen that has an innate resistance to some antibiotics. This bacterium is one of the most common causes of nosocomial infections that include surgical wound infections, burns, and urinary tract infections. The bacteria have been reportedly resistant to many antibiotics and have developed multidrug resistance (MDR). The objective of the study was to determine the resistance pattern of P. aeruginosa isolated from clinical samples of patients against some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…Among the beta lactams, the third generation cephalosporins, ceftazidime showed 21.8% of resistance while cefoperazone showed high level of resistance (45.9%), which may be contributed to the fact that it is the commonly used antimicrobial agent. In a study conducted by Rustini et al [14], ceftazidime showed 26.32% of resistance while cefoperazone showed 39.89% of resistance on par with our study. In our study, the fourth generation cephalosporin namely cefepime exhibited 25.7% of resistance.…”
Section: Discussionsupporting
confidence: 81%
“…Among the beta lactams, the third generation cephalosporins, ceftazidime showed 21.8% of resistance while cefoperazone showed high level of resistance (45.9%), which may be contributed to the fact that it is the commonly used antimicrobial agent. In a study conducted by Rustini et al [14], ceftazidime showed 26.32% of resistance while cefoperazone showed 39.89% of resistance on par with our study. In our study, the fourth generation cephalosporin namely cefepime exhibited 25.7% of resistance.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, the research by Behera et al (19) indicated resistance to this antibiotic to be more than 75%, while Rubin et al (20) reported the resistance rate of 39% to ceftriaxone, which is lower than our findings. In the present study, cefotaxime showed 67.1% resistance, which is higher than the reported rate by Rustini et al (21).…”
Section: Discussioncontrasting
confidence: 78%
“…Typical oxidase positive colonies growing on MacConkey agar and blood agar after incubating at 37 0 c for 24 hours were confirmed as P. aeruginosa using matrixassisted laser desorption ionization time-offlight (MALDI-TOF VITEK®MS), and antimicrobial susceptibility testing for the isolates were done by VITEK®2 system (bioMérieux, Inc., Durham, NC). The bacterial isolates were considered to exhibit MDR when they showed resistance to three or more antibiotics (Rustini et al, 2017).…”
Section: Microbiological Workupmentioning
confidence: 99%